Fluorescent Diarylethene Photoswitches—A Universal Tool for Super‐Resolution Microscopy in Nanostructured Materials. Issue 10 (11th January 2018) - Nevskyi, Oleksii; Sysoiev, Dmytro; Dreier, Jes; Stein, Simon Christoph; Oppermann, Alex; Lemken, Florian; Janke, Tobias; Enderlein, Jörg; Testa, Ilaria; Huhn, Thomas; Wöll, Dominik
Abstract: Super‐resolution fluorescence microscopy allows for unprecedented in situ visualization of biological structures, but its application to materials science has so far been comparatively limited. One of the main reasons is the lack of powerful dyes that allow for labeling and photoswitching in materials science systems. In this study it is shown that appropriate substitution of diarylethenes bearing a fluorescent closed and dark open form paves the way for imaging nanostructured materials with three of the most popular super‐resolution fluorescence microscopy methods that are based on different concepts to achieve imaging beyond the diffraction limit of light. The key to obtain optimal resolution lies in a proper control over the photochemistry of the photoswitches and its adaption to the system to be imaged. It is hoped that the present work will provide researchers with a guide to choose the best photoswitch derivative for super‐resolution microscopy in materials science, just like the correct choice of a Swiss Army Knife's tool is essential to fulfill a given task. Abstract : Super‐resolution imaging of nanostructured materials can be achieved with different super‐resolution fluorescence microscopy techniques when appropriate diarylethene derivatives are used. The photophysics and photochemistry of the dye can be adapted to gain optimal imaging conditions for localization‐based stochastic, scanning‐based deterministic, or image‐correlation methods with their specific strengths.